Self- conscious, extraversion and neuroticism and perception of painting art - Ślaski, Sławomir; Rudowski, Tomasz; Jastrzębski, Jarosław; Zaborowski, Zbigniew (Studia Psychologica: Theoria et praxis, 2007)
The authors of this article analyze connections between self- awareness (its individual, defensive, reflective and outer form), extraversion, neuroticism and perception of painting art. The correlations between reflective, defensive, outer forms of self- awareness, extraversion, neuroticism and perception of painting art were verified, but the relations between extraversion, neuroticism, the individual form of self-awareness and perception of painting art were not confirmed.